2006
DOI: 10.1111/j.1365-2729.2006.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I totally agree with you’: gender interactions in educational online discussion groups

Abstract: This paper discusses findings from an extensive project examining gender, language and computer‐mediated communication (CMC) in the context of undergraduate psychology courses. The contributions of 197 introductory psychology students (148 females, 49 males) participating in asynchronous CMC as part of their course were collated and coded for their language content using a qualitative content analysis procedure in Atlas.ti 4.2. Nearly 700 postings were characterised according to gender on the basis of seven ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 27 publications
5
29
1
5
Order By: Relevance
“…Prior studies revealed gender differences in the online text-based communication pattern and discourse. That is, females are more likely than males to express agreement and respond positively in online communication (Guiller & Durndell, 2006;Guiller & Durndell, 2007), probably because females tend to care more about interrelationships (Tannen, 1991) and connection with peers (Ching & Hsu, 2015). Playing a role may have greater impact on females in terms of alleviating their interpersonal barriers of critiquing peers and promoting psychological safety in the learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies revealed gender differences in the online text-based communication pattern and discourse. That is, females are more likely than males to express agreement and respond positively in online communication (Guiller & Durndell, 2006;Guiller & Durndell, 2007), probably because females tend to care more about interrelationships (Tannen, 1991) and connection with peers (Ching & Hsu, 2015). Playing a role may have greater impact on females in terms of alleviating their interpersonal barriers of critiquing peers and promoting psychological safety in the learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly due to student maturity and gendered concern for the feelings of others. As Guiller and Durndell (2006) found, women were more likely to express agreement than disagreement. There was, however, a ghost in the first discussion.…”
Section: Group 2 Discussionmentioning
confidence: 63%
“…If expression of critique is more difficult for women, the option to critique namelessly in online discussion may encourage freer expression. Given similar findings by Guiller and Durndell (2006), further exploration of student interaction patterns and gender is recommended.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Traditionally, and as Lakoff (2004) has remarked, women are said to have no sense of humour. In online discussion groups, scholars such as Guiller and Durndell (2006) have identified more instances of humour in men's participation in online discussion groups. In their study, more males than females sent messages containing humour.…”
Section: Discussionmentioning
confidence: 99%